2018
DOI: 10.1021/acssuschemeng.8b05276
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Thieno[2,3-d]pyrimidin-4(3H)-ones via a Catalytic Four-Component Reaction of Ketones, Ethyl Cyanoacetate, S8, and Formamide

Abstract: Thieno[2,3-d]pyrimidin-4(3H)-ones are important pharmacophores that previously required a three step synthesis with two chromatography steps. We herein report a green approach to the synthesis of this pharmacologically important class of compounds via a catalytic four-component reaction using a ketone, ethyl cyanoacetate, S8 and formamide. The reported reaction is characterized by step economy, reduced catalyst loading and easy purification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Among the numerous methods available in the literature for the synthesis of nitrogenbearing derivatives, multicomponent reactions (MCRs) are the most advantageous as they offer high atom economy, and provide access to highly complex molecules through multiple bond formation efficiencies. [1][2][3][4][5][6][7][8][9][10] Generally, these techniques avoid the purication and isolation of the intermediates, which minimizes solvent waste and enhances the eco-compatibility of the protocol. Spiro compounds are well-known due to their inherent three-dimensional structure in which the fusion point of the bicyclic system shares a single atom.…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous methods available in the literature for the synthesis of nitrogenbearing derivatives, multicomponent reactions (MCRs) are the most advantageous as they offer high atom economy, and provide access to highly complex molecules through multiple bond formation efficiencies. [1][2][3][4][5][6][7][8][9][10] Generally, these techniques avoid the purication and isolation of the intermediates, which minimizes solvent waste and enhances the eco-compatibility of the protocol. Spiro compounds are well-known due to their inherent three-dimensional structure in which the fusion point of the bicyclic system shares a single atom.…”
Section: Introductionmentioning
confidence: 99%
“…In heterocyclic chemistry, nitrogen-containing spiro compounds show various pharmacological applications. , Some of them are used as anti-HIV, antifungal, , anticancer, , antibacterial, and cytotoxic agents . In the present scenario, multicomponent reactions are promising tools for the construction of novel organic frameworks. In our current study, we explored a novel one-pot reaction of 3,4-methylenedioxyaniline, N , N -dimethylbarbituric acid, and aldehydes. A careful study of previously reported related literature discloses pioneering works for the one-pot reaction of 3,4-methylenedioxyaniline,1,3-cyclodione, and aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 1q was synthesized in three steps starting with a one-pot synthesis of thieno [2,3-d]pyrimidin-4-ol 4 via the Gewald reaction. 11 Compound 4 was subsequently converted to 4-chloro derivative 5 by treating with phosphoryl chloride. Nucleophilic substitution with 2-fluorophenol afforded the desired product 1q.…”
Section: ■ Chemistrymentioning
confidence: 99%